PENGARUH ORGANIZATIONAL JUSTICE SERTA JOB INSECURITY TERHADAP JOB SATISFACTION PEGAWAI KONTRAK PADA PT. WICO INTERNA, SINGARAJA-BALI - Komang Aris Yasadiputra; Made Surya Putra (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2014)
This study aims is to determine the effect of Organizational Justice and Job Insecurity on contract employee at PT. Wico Interna, Singaraja, Bali. Job Satisfaction on contract employees is important to note, because Job Satisfaction will give employees encouragement to work optimally in resolving any issues that arise. Job satisfaction is a set of employees feelings about their jobs . There are several variables that can affect Job Satisfaction , such as the Organizational Justice and Job Insecurity. 30 respondents were chosen using census method and analyzed using Partial Least Square. The analysis showed Organizational Justice positive effect on Job Satisfaction, Organizational Justice and the subsequent influence of Job Insecurity on Job Satisfaction showed a negative and significant effect